1994
DOI: 10.1111/j.1469-8137.1994.tb04003.x
|View full text |Cite
|
Sign up to set email alerts
|

Tansley Review No. 76 Helper bacteria: a new dimension to the mycorrhizal symbiosis

Abstract: SUMMARYThe symbiotic establishment of mycorrhizal fungi on plant roots is affected m various ways by the other microorganisms of the rhizosphere, and more especially by bacteria. This review discusses the case of some of these bacteria which consistently promote mycorrhizal development, leadmg to the concept of ' mycorrhization' helper bacteria (MHBs). Examples of MHB evidence are given from the literature, with special reference to the Douglas fir (Pseudotsuga menzeisii Mirb. Eranco)-Lacron'o laccata Scop, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
420
1
12

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 674 publications
(453 citation statements)
references
References 49 publications
15
420
1
12
Order By: Relevance
“…como ayudadores de micorrización de ciertas especies fúngicas como, por ejemplo, Laccaria laccata en abeto Douglas y Lactarius rufus en pino albar (Garbaye 1994, Poole et al 2001, Heinonsalo et al 2004. Sin embargo, es importante resaltar que la colonización bacterial de las ectomicorrizas muestra cierta especificidad entre el hospedero y el simbionte, pudiendo influenciar positiva o negativamente en la micorrización y por ende en el crecimiento de las plantas (Garbaye 1994, Poole et al 2001.…”
Section: Figuraunclassified
See 1 more Smart Citation
“…como ayudadores de micorrización de ciertas especies fúngicas como, por ejemplo, Laccaria laccata en abeto Douglas y Lactarius rufus en pino albar (Garbaye 1994, Poole et al 2001, Heinonsalo et al 2004. Sin embargo, es importante resaltar que la colonización bacterial de las ectomicorrizas muestra cierta especificidad entre el hospedero y el simbionte, pudiendo influenciar positiva o negativamente en la micorrización y por ende en el crecimiento de las plantas (Garbaye 1994, Poole et al 2001.…”
Section: Figuraunclassified
“…como ayudadores de micorrización de ciertas especies fúngicas como, por ejemplo, Laccaria laccata en abeto Douglas y Lactarius rufus en pino albar (Garbaye 1994, Poole et al 2001, Heinonsalo et al 2004. Sin embargo, es importante resaltar que la colonización bacterial de las ectomicorrizas muestra cierta especificidad entre el hospedero y el simbionte, pudiendo influenciar positiva o negativamente en la micorrización y por ende en el crecimiento de las plantas (Garbaye 1994, Poole et al 2001. Esta especificidad posiblemente está dada por el efecto combinado del tipo de suelo, el simbionte fúngico, la planta hospedero y la localización de las comunidades asociadas con las ectomicorrizas del árbol (Timonen et al 1999, Kozdrój et al 2007, haciendo entendible por qué no todas las bacterias inoculadas en P. patula colonizaron la raíz micorrizada o los diferentes niveles de micorrización encontrados.…”
Section: Figuraunclassified
“…The ubiquitous presence of prokaryotes (archaea, bacteria) and eukaryotes in the mycorrhizosphere and on the surface of ectomycorrhizae is well documented (Garbaye 1994;Bomberg and Timonen 2007;Calvaruso et al 2007;Frey-Klett et al 2007, Buée et al 2009). There are increasing reports on interactions of saprotrophic fungi and bacteria with ECM in nutrient release from complex substrates (Koide and Kabir 2001;Leake et al 2002;Nurmiaho-Lassila et al 1997;Timonen et al 1998;Wu et al 2005;Wu et al 2003).…”
Section: Factors Influencing the Enzyme Activities Of Ecm Communitiesmentioning
confidence: 99%
“…The ability of these bacteria to increase the pathogenicity of the fungi does not appear to have been tested. Nevertheless, it has been shown that for both arbuscular endomycorrhizal and ectomycorrhizal infections of plant roots some soil-borne bacteria, termed ' mycorrhizal helper bacteria ' (MHB) do play a positive role in the establishment of the fungal infections of plant roots (Garbaye, 1994 ;Frey-Klett et al, 1997). It is also suspected that bacteria commonly associated with surfaces of the attachment organs of species of the parasitic plant Orobanche may play a role in pathogenicity (Losner-Goshen et al, 1998).…”
Section: mentioning
confidence: 99%